The Role of Translation Competence and Cultural Value Among ELL in Cultural University - Farah Annisa; Wiwik Mardiana; Ahmad Iklil Saifulloh (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
English Language Learner might be good in English mainly on grammar, but that doesn’t determine that they are good in transforming information from source language to target language or so called translation. Translation is necessary since it is crucial for individuals who are not fluent in English. This research used descriptive qualitative in analyzing translation techniques and readability. The data sources were the English and Indonesian versions of a review text regarding the Harry Potter film series. The text was translated into Indonesian by nine ELLs (English students at Islamic University of Majapahit). The data were gathered by note-taking procedures and then evaluated using content analysis methods. Three readers served as raters, evaluating the readability of the translated review content. According to the findings, the ELLs used 13 techniques, the most dominant of which was amplification (22.81%), followed by reduction (20.80%) and borrowing. The ELLs' translation text had a high readability score (score 3) ranging from 23.14% to 0.59%. This data reveals that ELLs provided readable translation results on average. Furthermore, the average readability value has been classified as highly readable.